Effect of fat content on sensory and physico‐chemical properties of laboratory‐pasteurised calcium‐ and vitamin D‐fortified mixture of cow and buffalo milk. (5th September 2014) - Kaushik, Ravinder; Sachdeva, Bhawana; Arora, Sumit; Gupta, Chitra
<x xml:space="preserve">Abstract</x> The influence of milk fat on physico‐chemical properties of calcium and vitamin D‐fortified milk was investigated. Sensory scores, curd tension, viscosity, rennet coagulation time and TBA value increased with the increase in fat content. Calcium and vitamin D fortification had no effect on sensory scores, whereas a significant increase was observed in curd tension and viscosity. The TBA value of fortified milk was significantly lower than that of the unfortified milk. The rennet coagulation time of milk increased significantly with addition of calcium phosphate, whereas calcium citrate fortification had no significant effect. All milk samples were stable to alcohol.